Microsoft Data Protection Manager 2010 - Buchanan, Steve (Packt Publishing, 2011)
This book is a very valuable add-on to the available documentation and a must have for everybody who wants to investigate the possibilities of Data Protection Manager and for those who need to implement and work with it on a daily basis. This book will provide you with additional ideas, possibilities and information that is needed when you work with DPM as your backup product of choice. What is also interesting is that he likes to use links to additional information from the field instead of using the Microsoft links. This however could be also dangerous for dead links.